ANALYSIS OF SECTORAL ADVANTAGES OF PALM OIL AND RUBBER COMMODITIES IN MUARO JAMBI REGENCY, JAMBI PROVINCE - Masrida Zasriati; Osi Hayuni Putri; Fitrina Afrianti; Idul Nilyan Fitri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The background of this research is that Muaro Jambi Regency is a Regency that has a potential sector, namely the plantation sector, especially palm oil and rubber commodities. This can be seen from the data from the Central Statistics Agency (BPS) of Jambi Province. The analysis method used is Location Quotient (LQ) Analysis. The type of data used in this study is secondary data, all data used in this study includes the area of ​​oil palm and rubber, production and productivity of oil palm and rubber plantations, production of oil palm and rubber plantations and production data for the last six years, namely 2018 to 2023. The results of the Location Quotient (LQ) analysis show that in Muaro Jambi Regency as a base area for oil palm, namely (i) 2018 with an LQ value of 1.13 (ii) 2020 with an LQ value of 1.19 (iii) 2021 with an LQ value of 1.16 (iv) 2022 with an LQ value of 1.06 (v) 2029 with an LQ value of 1.08. The results of the analysis show that oil palm is a base sector while rubber is a non-base sector.